Dual-beam laser traps in biology and medicine: When one beam is not enough - Whyte, Graeme; Lautenschlaeger, Franziska; Kreysing, Moritz; Boyde, Lars; Ekpenyong, Andrew; Delabre, Ulysse; Chalut, Kevin; Franze, Kristian; Guck, Jochen (Proceedings of SPIE - The International Society for Optical Engineering, 2010)
Optical traps are nowadays quite ubiquitous in biophysical and biological studies. The term is often used synonymously with optical tweezers, one particular incarnation of optical traps. However, there is another kind of optical trap consisting of two non-focused, counter-propagating laser beams. This dual-beam trap predates optical tweezers by almost two decades and currently experiences a renaissance. The advantages of dual-beam traps include lower intensities on the trapped object, decoupling from imaging optics, and the possibility to trap cells and cell clusters up to 100 microns in diameter. When used for deforming cells this trap is referred to as an optical stretcher. I will review several applications of such traps in biology and medicine for the detection of cancer cells, sorting stem cells, testing light guiding properties of retinal cells and the controlled rotation of cells for single cell tomography. © 2010 SPIE.
CRIS-Team Scopus Importer:2020-08-12
Keywords: Cell mechanics; Optical cell rotator; Optical stretcher; Optical trap; Optical tweezers; Retina optics; Tomography